ASPECTS OF AESTHETIC REHABILITATION BY IMPLANT-SUPPORTED FIXED PROSTHESIS IN A COMPLETE EDENTULOUS CASE - Maria-Antonela Beldiman; Monica Tatarciuc; Diana Diaconu-Popa; Georgiana Macovei; Violina Budu; Laura Elisabeta Checheriță; Liana Aminov; Odette Luca (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study Treatment possibilities for complete edentulous cases by placing implants result in superior functional results, for better aesthetics, as well as stability, strength and support of prostheses and improved masticatory efficiency. Materials and methods The objective of this study is to highlight the importance of fabricating appropriate implant-based fixed prostheses through the appropriate selection and design of all their components in the treatment plan for our patient, with total edentulousness. A 56-year-old patient presented himself at the dental office, with complete edentulous status, in both arches, and the treatment was the "Fast and Fixed" option of "All on 6" in the maxilla jaw and "All on 4" in the mandible, with framework from zirconia and PEEK, respectively. Results The rehabilitation of complete edentulous status with fixed implant supported prostheses is one of the challenging treatments, because of the aesthetic and functional factors that should be considered. Conclusions There is a superior prognosis of oral rehabilitation with implants compared to traditional methods, and statistical data shown a high success rate of around 95% for 10 years. Fixed restorative systems on dental implants are considered the ideal solution for replacing missing teeth in the case of total edentulous arches.